Towards a Design Flow for Reversible Logic - Wille, Robert; Drechsler, Rolf.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The development of computing machines found great success in the last decades. But the ongoing miniaturization of integrated circuits will reach its limits in the near future. Shrinking transistor sizes and power dissipation are the major barriers in the development of smaller and more powerful circuits. Reversible logic provides an alternative that may overcome many of these problems in the future. For low-power design, reversible logic offers significant advantages since zero power dissipation will only be possible if computation is reversible. Furthermore, quantum computation profits from enhancements in this area, because every quantum circuit is inherently reversible and thus requires reversible descriptions. However, since reversible logic is subject to certain restrictions (e.g. fanout and feedback are not directly allowed), the design of reversible circuits significantly differs from the design of traditional circuits. Nearly all steps in the design flow (like synthesis, verification, or debugging) must be redeveloped so that they become applicable to reversible circuits as well. But research in reversible logic is still at the beginning. No continuous design flow exists so far. In Towards a Design Flow for Reversible Logic, contributions to a design flow for reversible logic are presented. This includes advanced methods for synthesis, optimization, verification, and debugging. Formal methods like Boolean satisfiability and decision diagrams are thereby exploited. By combining the techniques proposed in the book, it is possible to synthesize reversible circuits representing large functions. Optimization approaches ensure that the resulting circuits are of small cost. Finally, a method for equivalence checking and automatic debugging allows to verify the obtained results and helps to accelerate the search for bugs in case of errors in the design. Combining the respective approaches, a first design flow for reversible circuits of significant size results.
Preliminaries -- Synthesis of Reversible Logic -- Exact Synthesis of Reversible Logic -- Embedding of Irreversible Functions -- Optimization -- Formal Verification and Debugging -- Summary and Conclusions.
Keywords: Engineering; Systems engineering; Engineering; Circuits and Systems